A Prospective Single-Arm Cohort Study of Immune-mediated Seizures/Epilepsy Without Encephalopathy (ISEWE) in Children from a Tertiary Care Hospital in South India - Basavanagowda Thanuja; Mahesh Kamate (Annals of Indian Academy of Neurology)
Acute-onset seizures in children pose a diagnostic and therapeutic dilemma. Some epilepsy cases presenting with seizures but without encephalopathy, though treatable with immunotherapy, are often missed due to lack of suspicion of immune mechanism in the context of absent encephalitis. A prospective study was conducted on premorbidly normal children with new-onset seizures occurring in clusters, with normal neuroimaging. Investigations included electroencephalogram (EEG), cerebrospinal fluid examination, and testing for autoantibodies. All cases received methylprednisolone pulse therapy along with antiseizure medications (ASMs), followed by monthly dexamethasone oral pulse therapy. Fifteen cases were enrolled (11 males, four females). Mean age at seizure onset was 4.6 years. Focal seizures were present in 13/15 (86.7%) cases. Magnetic resonance imaging of the brain was normal in all. EEG showed interictal epileptiform discharges in 12 cases (focal in nine) and ictal record in two cases. On monthly oral steroids, number of ASMs could be reduced. Eight cases never had a relapse, while seven did have it. Relapses were more common if more than three ASMs were tried and less if steroids were started within 30 days. Immune-mediated seizures/epilepsy without encephalopathy is a new, important, and treatable entity. Early diagnosis and institution of immunotherapy results in significant improvement in seizure control and also reduces the need for long-term polytherapy. Awareness of this entity is crucial, especially when premorbidly normal children present with new-onset clusters of refractory seizures.